Spatial Interaction of Archaeal Ammonia-Oxidizers and Nitrite-Oxidizing Bacteria in an Unfertilized Grassland Soil - Stempfhuber, Barbara; Richter-Heitmann, Tim; Regan, Kathleen M.; Kölbl, Angelika; Wüst, Pia K.; Marhan, Sven; Sikorski, Johannes; Overmann, Jörg; Friedrich, Michael W.; Kandeler, Ellen; Schloter, Michael (Frontiers in Microbiology, 2016)
Interrelated successive transformation steps of nitrification are performed by distinct microbial groups – the ammonia-oxidizers, comprising ammonia-oxidizing archaea (AOA) and bacteria (AOB), and nitrite-oxidizers such as Nitrobacter and Nitrospira, which are the dominant genera in the investigated soils. Hence, not only their presence and activity in the investigated habitat is required for nitrification, but also their temporal and spatial interactions. To demonstrate the interdependence of both groups and to address factors promoting putative niche differentiation within each group, temporal and spatial changes in nitrifying organisms were monitored in an unfertilized grassland site over an entire vegetation period at the plot scale of 10 m². Nitrifying organisms were assessed by measuring the abundance of marker genes (amoA for AOA and AOB, nxrA for Nitrobacter, 16S rRNA gene for Nitrospira) selected for the respective sub-processes. A positive correlation between numerically dominant AOA and Nitrospira, and their co-occurrence at the same spatial scale in August and October, suggests that the nitrification process is predominantly performed by these groups and is restricted to a limited timeframe. Amongst nitrite-oxidizers, niche differentiation was evident in observed seasonally varying patterns of co-occurrence and spatial separation. While their distributions were most likely driven by substrate concentrations, oxygen availability may also have played a role under substrate-limited conditions. Phylogenetic analysis revealed temporal shifts in Nitrospira community composition with an increasing relative abundance of OTU03 assigned to sublineage V from August onwards, indicating its important role in nitrite oxidation.